Kinematic analysis of the barbell during the snatch movement of Japanese weight lifters - Ikeda, Y.; Matsuo, A.; Tachi, M.; Funato, K.; Fuchimoto, T.; Kikuta, M. (Japanese Journal of Elite Sports Support, 2010)
This study investigated the kinematic characteristics of the snatch technique by analyzing Japanese weightlifter`s trajectories of the barbell. Subjects were male Japanese weightlifters (n=48) with different lifting abilities who participated in weightlifting competition. Among these subjects, 8 lifters participated in the 2007 world championships. Trajectories of the barbell during snatch lifts in 8 weight categories were videotaped. For comparison of the lifting technique, 8 weight categories were integrated into four weight categories; Light weight, Middle weight, Heavy weight and Super heavy weight which were then divided into an upper group and lower group based on the lifting record in each category. Concerning the results of the barbell kinematics, there was no apparent difference between the upper groups and lower groups. In addition, kinematic characteristics of the best and worst lifters did not necessarily equate with those in the upper and lower groups. As the best lifter`s primary feature, barbell trajectories, except for two lifters in the 56kg and 94kg class, crossed the vertical reference line projected upward from the start position. They demonstrated small horizontal displacement of barbell compared with that of the worst lifters. In comparison with world-class weightlifters, there were differences in the barbell`s trajectory, vertical acceleration during transition and the angle of resultant acceleration at the first pull and second pull. These findings indicate that the difference in performance between world-class lifters and Japanese lifters was derived not only from strength and power production but also from lifting technique.